2005
DOI: 10.1093/humrep/dei310
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy: does it affect ovarian follicular status and responsiveness to controlled ovarian stimulation?

Abstract: BACKGROUND: Myotonic dystrophy (MD) is characterized by myotonia, multisystemic lesions and hypogonadism.In women, the relationship between MD and infertility remains controversial. This study investigated the ovarian status and response to controlled ovarian stimulation (COS) in MD women entering our preimplantation genetic diagnosis programme. METHODS: We elected to compare MD patients with X-linked disorders (XLD) carriers, given that XLD have not been shown to affect ovarian status. On the one hand, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…After 2004, only three couples were enrolled in the program, and seven cycles were started, yielding five oocyte retrievals and four embryo transfers; no pregnancies occurred. Incidentally, a significantly decreased ovarian response was also found in women affected by myotonic dystrophy (35).…”
Section: Discussionmentioning
confidence: 91%
“…After 2004, only three couples were enrolled in the program, and seven cycles were started, yielding five oocyte retrievals and four embryo transfers; no pregnancies occurred. Incidentally, a significantly decreased ovarian response was also found in women affected by myotonic dystrophy (35).…”
Section: Discussionmentioning
confidence: 91%
“…1 Expected (∎) vs real (•) cumulative delivery rate (percentage) study group total (female + male affected Steinert patients) (n=78) There are no significant differences between any of these results commonly been accepted as normal, although oligomenorrhea, abortions and early menopause have been reported [23]. In contrast with this, Feyereisen and colleagues suggested in a recent small series of patients that ovarian response is lower than in controls based on an observed significant delay in day of hCG administration and a higher prevalence of poor quality embryos in the DM1 group [24]. Another small study by Sahu et al similarly suggested a reduced ovarian reserve and ovarian response [25].…”
Section: Discussionmentioning
confidence: 92%
“…Marchini et al (19) reported that sterility or hypogonadism were not related to the number of CTG repeats. Feyereisen et al (10) found no statistically significant correlation between the ovarian status, response to COS, or cancellation rate for insufficient response and (CTG) triplet repeats.…”
Section: Discussionmentioning
confidence: 97%
“…Feyereisen et al compared the ovarian response of women with DM1 with women with X-linked disorder carriers. They concluded that women with DM1 have a moderate decrease in fertility (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation